Pengaruh Komitmen Organisasi Dan Kompensasi Terhadap Kinerja Guru - Hibata, Oktoleni Jein; Posi, Sahrul Hi; Manoma, Suharli (JIMAD : Jurnal Ilmiah Multidisiplin, 2024)
The management of human resources in an agency environment has a very important role. Human resources are the main factor in planning, directing and supervising all activities. Given the importance of the human resource factor, each agency is required to improve the performance of its employees so that they are qualified and productive to run the agency. The purpose of this study was to determine the effect of organizational commitment and compensation on teachers. The research method used in this study is a quantitative method. The population used as a sample in this study amounted to 26 people as respondents. Data collection was carried out by distributing questionnaires to teachers. The analysis used is multiple linear regression analysis technique. The results of the analysis show that. Simultaneous organizational commitment has a positive and significant effect on teacher performance, while compensation simultaneously has a negative and insignificant effect on teacher performance.